Algeria : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2013)
This paper studies the main sources for growth in Algeria within a cross-country analysis and draws policy recommendations to support faster growth. In Section 1, a growth accounting exercise framework has been explained, and in Section 2, the determinants for growth are identified. This study examines the factors behind the recent increase in inflation and the policies that should be implemented to bring inflation back to the level targeted by the monetary authorities. Two approaches used to explore the determinants of inflation were discussed.